Generation and trapping of electron-deficient 1, 2-cyclohexadienes. Unexpected hetero-Diels–Alder reactivity. Issue 2 (10th December 2020) - Wang, Baolei; Constantin, Marius-Georgian; Singh, Simarpreet; Zhou, Yuqiao; Davis, Rebecca L.; West, F. G.
Abstract : Keto-substituted 1, 2-cyclohexadienes undergo a novel dimerization process and can be trapped with various furan-based 1, 3-dienes or enamine dienophiles. Abstract : Keto-substituted 1, 2-cyclohexadienes were generated by base-mediated (KO t -Bu) elimination, and found to dimerize via an unprecedented formal hetero-Diels–Alder process, followed by hydration. These highly reactive cyclic allene intermediates were also trapped in Diels–Alder reactions by furan, 2, 5-dimethylfuran, or diphenylisobenzofuran to afford cycloadducts with high regio- and diastereoselectivity, and could also be intercepted in a hetero-Diels–Alder process with enamine dienophiles. Endo / exo stereochemistry was unambiguously determined via X-ray crystallography in the case of nitrile-substituted 1, 2-cyclohexadiene. DFT calculations indicate that the novel hetero-Diels–Alder processes observed with these allenes occur via a concerted asynchronous cycloaddition mechanism.